Religious Moderation from the Perspective of Islamic Law and Its Application in Education - Sri Wahyuni; Dafril; Syafrianto; Rusydi; Riki Saputra (Suria Academic Press, 2026)
Religious moderation has become an important discourse in contemporary Islamic studies, particularly in the context of pluralistic societies facing challenges of radicalism, intolerance, and religious polarization. This study aims to analyze the concept of religious moderation from the perspective of Islamic law and examine its application within Islamic education. The study employs a qualitative library research approach by examining various sources related to Islamic teachings, Sharia principles, moderation theory, and educational practices. The findings reveal that religious moderation in Islam is deeply rooted in the concept of wasathiyah, which emphasizes balance, justice, tolerance, equality, and consultation. These values are reflected in the principles of tawassuth, tasamuh, i’tidal, tawazun, musawah, and syura, all of which form the foundation of a moderate Islamic worldview. In the perspective of Sharia and Islamic law, moderation is manifested through flexibility, contextual legal reasoning, and the orientation toward public welfare (maslahah) and justice. The study also shows that the implementation of moderation in Islamic education can be carried out through curriculum development, dialogical learning methods, character education, and the creation of inclusive educational environments. However, the application of religious moderation continues to face challenges such as radicalism, weak religious literacy, politicization of religion, and misconceptions regarding moderation itself. Therefore, strengthening moderation through education is essential in developing Muslims who are faithful, tolerant, inclusive, and capable of contributing to social harmony and peaceful coexistence in multicultural societies.